Loss of RAB1B promotes triple-negative breast cancer metastasis by activating TGF-β/SMAD signaling - Jiang, Hong-Lin (Oncotarget, 2015)
Triple-negative breast cancer (TNBC) is a highly aggressive tumor subtype associated with a poor prognosis. The mechanism involved in TNBC progression remains largely unknown. To date, there are no effective therapeutic targets for this tumor subtype. In this study, by performing quantitative proteomic analyses in highly metastatic and parental breast cancer cell line, we found that RAB1B, a member of the RAS oncogene family, was significantly down-regulated in highly metastatic breast cancer cells. Moreover, down-regulation of RAB1B was also found to promote the proliferation and migration of TNBC cells in vitro and in vivo. Mechanistically, loss of RAB1B resulted in elevated expression of TGF-β receptor 1 (TβR1) through decreased degradation of ubiquitin, increased levels of phosphorylated SMAD3 and TGF-β-induced epithelial-mesenchymal transition (EMT). Furthermore, low RAB1B expression correlated with poor prognosis in breast cancer patients. Taken together, our findings reveal that RAB1B acts as a metastasis suppressor in TNBC by regulating the TGF-β/SMAD signaling pathway and RAB1B may serve as a novel biomarker of prognosis and the response to anti-tumor therapeutics for patients with TNBC.